2019
DOI: 10.1111/tpj.14594
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of red‐light‐induced stomatal opening in Arabidopsis thaliana: Coupling with abscisic acid and jasmonic acid metabolism

Abstract: Summary Environmental stimuli‐triggered stomatal movement is a key physiological process that regulates CO2 uptake and water loss in plants. Stomata are defined by pairs of guard cells that perceive and transduce external signals, leading to cellular volume changes and consequent stomatal aperture change. Within the visible light spectrum, red light induces stomatal opening in intact leaves. However, there has been debate regarding the extent to which red‐light‐induced stomatal opening arises from direct guard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 82 publications
0
27
0
Order By: Relevance
“…Red light pulses (500 µmole/m 2 s) on a red background did not cause a similar reaction. In line with these findings, Zhu et al [48] found that blue light-induced stomatal opening required low light intensity and a short duration of illumination as compared with red light-induced stomatal opening [48].…”
Section: Stomatal Opening and Lightmentioning
confidence: 80%
See 2 more Smart Citations
“…Red light pulses (500 µmole/m 2 s) on a red background did not cause a similar reaction. In line with these findings, Zhu et al [48] found that blue light-induced stomatal opening required low light intensity and a short duration of illumination as compared with red light-induced stomatal opening [48].…”
Section: Stomatal Opening and Lightmentioning
confidence: 80%
“…Red light induces stomatal opening via photosynthesis in the mesophyll and guard cell chloroplasts and decreases the intercellular CO 2 concentration, therefore, red light acts both as a signal and an energy source [47]. The red-light-induced stomatal opening may result from a combination of both guard cell responses to the reduction in intercellular CO 2 and a direct response of the chloroplasts located in the guard cells to red light [46,48,49]. It has been thought to be the main mechanism that coordinates stomatal behaviour in relation to photosynthesis [50].…”
Section: Stomatal Opening and Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that TAGs are used as a vital energy source, stimulating ATP and malate production through β-oxidation and TCA cycle (Vavasseur and Raghavendra, 2005;Daloso et al, 2017). Furthermore, a recent study systematically examined red light-induced metabolic changes in GCs of Arabidopsis, showing that red light-induced stomatal opening is correlated with decreased contents of ABA and jasmonic acid (JA) in GCs in addition to TCA cycle and carbon homeostasis (Zhu et al, 2020). It will be interesting to investigate how light and phytohormone signaling cross-talk in regulating stomatal movement.…”
Section: Light-induced Metabolic Changes In Guard Cells Stimulate Stomentioning
confidence: 99%
“…It is also unclear whether this function is conserved across angiosperms. The angiosperm PAR response might reflect a combination of 4 mesophyll signals and largely unknown pathways involving guard cell photosynthesis and/or metabolism (Lawson et al, 2008;Messinger et al, 2006;Olsen et al, 2002;Zhu et al, 2020), although the mesophyll component is often dominant (Fujita et al, 2013;Mott et al, 2008;Roelfsema et al, 2002). In seed-free plants, the mesophyll-based response to light is apparently absent and the PAR stomatal response is entirely dependent on guard cell photosynthesis and/or metabolism (Doi and Shimazaki, 2008;McAdam and Brodribb, 2012).…”
Section: Introductionmentioning
confidence: 99%